2017
DOI: 10.1155/2017/6302869
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Excess Iodide Intake on Salivary Glands in a Swiss Albino Mice Model

Abstract: Iodine is an important micronutrient required for nutrition. Excess iodine has adverse effects on thyroid, but there is not enough information regarding its effect on salivary glands. In addition to food and iodized salt, skin disinfectants and maternal nutritional supplements contain iodide, so its intake could be excessive during pregnancy, lactation, and infancy. The aim of this work was to evaluate the effect of excess iodide ingestion on salivary glands during mating, gestation, lactation, and postweaning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…While lower dose of iodide intake is safe and associated with normal thyroid function, recent works have proven that alterations in thyroid function are associated with high iodide supplementation in maternal rats and their offspring [ 48 ]. Other findings show that treatment in vivo with an excess of iodide can induce the blockade of thyroid hormone biosynthesis [ 49 ] and excess of iodide could induce mononuclear infiltration in salivary gland as recently indicated in a Swiss albino mouse model [ 50 ] These results question whether iodide supplementation would work to boost anti-influenza defenses.…”
Section: Discussionmentioning
confidence: 99%
“…While lower dose of iodide intake is safe and associated with normal thyroid function, recent works have proven that alterations in thyroid function are associated with high iodide supplementation in maternal rats and their offspring [ 48 ]. Other findings show that treatment in vivo with an excess of iodide can induce the blockade of thyroid hormone biosynthesis [ 49 ] and excess of iodide could induce mononuclear infiltration in salivary gland as recently indicated in a Swiss albino mouse model [ 50 ] These results question whether iodide supplementation would work to boost anti-influenza defenses.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, previous research has reported a link between thyroid illness and the salivary glands. Saliva contains a greater quantity of iodine than that in serum (27). Salivary glands, stomach, and thyroid share a sodium iodide transporter (NIS) capable of concentrating iodine ions (28).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have implicated iodine deficiency in immune dysfunctions ( 56 ). Excess iodine has been reported to induce alterations of the salivary glands, including lymphocytic infiltrations ( 58 ), in an animal model. In vitro , I − is another substrate for sialoperoxidase, myeloperoxidase or lactoperoxidase in antimicrobial systems.…”
Section: Oral Peroxidases: Enzymes and Substratesmentioning
confidence: 99%